Leading Poetic Features of Jamal Kamal’s Octave Genre - Karshiyev Komil Abdikarimovich (International Journal on Integrated Education, 2021)
The article discusses the role of the octave genre in Jamal Kemal's poetry, its unique poetic features, lyrical miniature landscapes, lines of associative thinking, and artistic appeal.